Polityka energetyczna Unii Europejskiej w kontekście problematyki bezpieczeństwa gospodarczego - Tomaszewski, Krzysztof (Przegląd Politologiczny, 2018)
The article is an analysis of energy policy in the context of the economic security of the European Union. One of the key challenges facing the EU is to ensure the economic security both of its members, as well as of the entire organization. The energy sector and energy policy are an integral part of the European Union’s development strategy. They may contribute to improved effectiveness of the integration process or to the failure of the European project. The aim of this article is to examine the challenges and problems that are associated with the formation of European energy policy. For the integration project to succeed, it is imperative for this policy to be properly planned and managed. Failing to implement appropriate mechanisms and actions to ensure energy security (taken at Community level), poses threats of strengthened national particularities in the EU, economic slowdown and, consequently, a slow erosion of the European political system.